The Galaxy platform for accessible, reproducible and collaborative biomedical analyses: 2020 update. Issue Volume 48:Issue W1(2020) (1st June 2020) - Jalili, Vahid; Afgan, Enis; Gu, Qiang; Clements, Dave; Blankenberg, Daniel; Goecks, Jeremy; Taylor, James; Nekrutenko, Anton
Abstract: Galaxy (https://galaxyproject.org ) is a web-based computational workbench used by tens of thousands of scientists across the world to analyze large biomedical datasets. Since 2005, the Galaxy project has fostered a global community focused on achieving accessible, reproducible, and collaborative research. Together, this community develops the Galaxy software framework, integrates analysis tools and visualizations into the framework, runs public servers that make Galaxy available via a web browser, performs and publishes analyses using Galaxy, leads bioinformatics workshops that introduce and use Galaxy, and develops interactive training materials for Galaxy. Over the last two years, all aspects of the Galaxy project have grown: code contributions, tools integrated, users, and training materials. Key advances in Galaxy's user interface include enhancements for analyzing large dataset collections as well as interactive tools for exploratory data analysis. Extensions to Galaxy's framework include support for federated identity and access management and increased ability to distribute analysis jobs to remote resources. New community resources include large public servers in Europe and Australia, an increasing number of regional and local Galaxy communities, and substantial growth in the Galaxy Training Network.